Territorial Impact Assessment and Cross-Border Cooperation - Medeiros, Eduardo (2018)
Impact Assessment procedures have gained increasing attention from the European Commission (EC), as fundamental tools in providing evidence of the potential impacts of European Union (EU) financed projects/programmes/policies. Yet, only recently, the Territorial Impact Assessment (TIA) of EU directives and Policies have gained a broader support from the EC, as a result of pivotal contributions from several ESPON projects in producing adequate TIA techniques/tools/methods (TEQUILA, Quick Check, EATIA). In the meantime, these tools are being perfected, alongside others (like the TARGET_TIA), in order to provide a more efficient and broader analysis of the evaluated project/programme/policy territorial impacts. Furthermore, there is a general agreement that TIA needs to take on account the different territorial levels (EU, national, regional, local), and should be applied in specific sector policies/programmes, which require more holistic evaluation procedures, as they have a strong territorial dimension. This is clear in the case of the Cross-Border Cooperation (CBC) programmes, due to their large scope of interventions on providing territorial development of the border areas, which in the EU encompass more that 60% of its territory. In light of this, this article proposes an adaptation of the TARGET_TIA technique to assess the territorial impacts of the CBC programmes, by focusing on the evaluation of the components of the CBC programmes specific goals: barrier effect reduction and territorial capital valorisation.